Geographic concordance of genetic barriers in New Zealand coastal marine species. Issue 12 (16th November 2021) - Arranz, Vanessa; Fewster, Rachel M.; Lavery, Shane D.
Abstract: Comparative phylogeography is recognized as a powerful tool to discern common patterns of connectivity across species, information that can be crucial in assisting the design of protected area networks. Previously, qualitative analyses have been undertaken in New Zealand waters in order to find concordance in marine dispersal barriers. This study presents the first attempt to quantitatively measure the congruence in genetic divergence breaks among 21 New Zealand marine coastal invertebrates, while accounting for the effects of variable sampling scale, life history traits and marker type. Previously recognized phylogeographic barriers to dispersal were found to be significant across species, such as the North–South Island differentiation and a northern genetic break at Cape Reinga. Low‐dispersal species exhibited additional locations of common significant divergence. Some of the differences in genetic barriers observed among species may be more related to the habitat type of the species (intertidal zone or subtidal) and the marker type used in the study (mitochondrial DNA or microsatellites), than to the dispersal traits of the species (high or low dispersal). Despite some limitations, the approach implemented here has significant advantages and permits the use of data from a wide variety of studies. This study provides the first quantitative insight into community‐wide genetic barriers within New Zealand's coastal marine ecosystem and provides directions for future investigations of this type in other regions.